2005
DOI: 10.1097/01.jnen.0000179050.54522.5a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Oxidative Stress in the Neocortex in Incidental Lewy Body Disease

Abstract: Oxidative stress has been well documented in the substantia nigra in Parkinson disease (PD), but little is known about oxidative damage, particularly lipoxidation, advanced glycation (AGE), and AGE receptors (RAGE) in other structures, including the cerebral cortex, in early stages of diseases with Lewy bodies. The present study was undertaken to analyze these parameters in the frontal cortex (area 8), amygdala, and substantia nigra in selected cases with no neurologic symptoms and with neuropathologically ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 51 publications
8
159
1
1
Order By: Relevance
“…This oxidative stress could in turn lead to lipid peroxidation and ultimately to HNE formation. There are several reports suggesting increased HNE modification in Parkinson disease (42,43,53). Because ␣-synuclein in its normal physiological situation is bound to membranes containing substantial unsaturated fatty acyl chains, it will inevitably be exposed to significant amounts of HNE, so these observations are consistent with a potentially toxic effect of HNE modification of ␣-synuclein.…”
Section: Hne Modification Of ␣-Synuclein Results In Conformationalmentioning
confidence: 99%
“…This oxidative stress could in turn lead to lipid peroxidation and ultimately to HNE formation. There are several reports suggesting increased HNE modification in Parkinson disease (42,43,53). Because ␣-synuclein in its normal physiological situation is bound to membranes containing substantial unsaturated fatty acyl chains, it will inevitably be exposed to significant amounts of HNE, so these observations are consistent with a potentially toxic effect of HNE modification of ␣-synuclein.…”
Section: Hne Modification Of ␣-Synuclein Results In Conformationalmentioning
confidence: 99%
“…Studies in the substantia nigra and midbrain have shown increased levels of lipid hydroperoxides (47) and 4-hydroxy-2-nonenal (an end product of lipid peroxidation) (48), as well as changes in PUFAs susceptible for lipid peroxidation, leading to increased generation of malondialdehyde and hydroperoxides (20,49). Interestingly, oxidative damage in the substantia nigra is present in iPD (20). Only recently, evidence for lipid peroxidation and oxidative damage in cortical structures was demonstrated in PD and iPD (20,50).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the highly peroxidizable docosahexaenoic acid (DHA) appears to be significantly increased in the frontal cortex in iPD and PD (20). Whether altered lipid composition affects highly specialized structures such as lipid rafts in PD and iPD is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible pathomechanisms in Parkinson's disease Mitochondrial damage and oxidative stress Increased expression of 4--hydroxy--2--nonenal (HNE) (Yoritaka et al, 1996), decreased activity of mitochondrial complex I and a decreased amount of alpha--ketoglutarate dehydrogenase complex (KGDHC) in the pigmented neurons of the substantia nigra (Hattori et al, 1991;Mizuno et al, 1994) have been reported in affected patients. In the substantia nigra, decreased activity of catalase and peroxidase (Ambani et al, 1975) and increased amounts of protein carbonyls, 8--hydroxy--2'--deoxyguanosine (8--OHdG)/8--hydroxy--guanine (8--OHG), 4--hydroxynonenal--lysine and malondialdehyde--lysine (MDAL) (Alam et al, 1997a,b;Zhang et al, 1999;Dalfo et al, 2005) have been reported. 1--Methyl--4--phenyl--1,2,3,6--tetrahydropyridine (MPTP) was the first human parkinsonian agent to be characterized.…”
Section: Magnesium In Parkinson's Disease: An Update In Clinical and mentioning
confidence: 99%